Development of Cloud-Based Co-Parenting Strengthening System - Engel, Mychael Maoeretz; Setiawan, Jenny Lukito; Indriati, Lisa (JUITA: Jurnal Informatika, 2021)
Co-parenting emphasizes how couple manage their relationship in the parenting domains and carry out their role as parents. Based on research conducted by Feinberg and colleagues (2012), there are four overlapping domains of co-parenting: (1) child rearing agreement; (2) support/undermining partner’s parenting; (3) joint family management; and (4) division of labor. The interference of mobile-based technology is needed on the co-parenting relationship between the couple with reference to the four domains of co-parenting. The method used was the Systems Development Life Cycle (SDLC) model. It was divided into six stages of the process: requirement analysis, system design, implementation, system testing, system deployment, and system maintenance. In implementation, the system at an early stage has four main features: (1) child’s activity scheduling and reminder; (2) co-parenting’s education contents; (3) partner’s feedback; and (4) co-parenting’s assessment. The results that are proven by experts, agreed that educational content in the application is very necessary for more knowledge for parents, UI/UX design that is friendly and easy to understand by users, as well as the use of the latest reliable and flexible technology.